Demarginalizing the intersection of race and sex: A black feminist critique of antidiscrimination doctrine, feminist theory and antiracist politics - Crenshaw, Kimberle (The University of Chicago Legal Forum, 1989)
Keywords: afro-féminisme; amériques; antiracisme; approches et analyses; cours; discipline; droit; féminismes noirs; incontournable; intersectionnalité; militance; pol4212; premier cycle; projet charge mentale; racisme; ressource en ligne; régions géographiques; science politique et droit; systèmes d'oppressions; thématiques; états-unis

Justice, gender, and the family - Okin, Susan Moller (Basic Books, 1989)
This work is a feminist critique of modern political theory. The author sets out to show how the failure to apply theories of justice to the family not only undermines democratic values but has led to a major crisis over gender-related issues.
Keywords: amériques; approches et analyses; care; discipline; division sexuelle du travail; droit; droits des femmes*; famille; genre; mariage; maternité; militance; patriarcat; philosophie; ressource en ligne; régions géographiques; science politique et droit; sciences humaines; stéréotypes de genre; systèmes d'oppressions; thématiques; travail; états-unis